Uncover valuable information and solutions with IDNLearn.com's extensive Q&A platform. Discover reliable and timely information on any topic from our network of experienced professionals.
Answer:
x = 6+3y
y = y (any number)
the rest should follow the same steps
Step-by-step explanation:
2x-6y=12 -> divide both sides by 2 (GCF)
x-3y = 6 -> solve for x, because it has 1 as its coefficient, or the lowest coefficent
x = 6+3y
-5x+15y=-30 -> divide both sides by 5
-1x+3y=-6 -> plug in x from previous equation
-(6+3y) + 3y = -6
-6-3y+3y = -6
y = y